The use of geographically weighted regression to improve information from satellite night light data in evaluating the economic effects of the 2010 FIFA World Cup. Issue 4 (2nd October 2022) - Coulibaly, Thierry Yerema; Wakamatsu, Mihoko Tegawa; Managi, Shunsuke
ABSTRACT: Developing countries lack subnational data to assess mega-events. Accordingly, an economic proxy is developed to quantify city-level income growth of economies of the South African cities that hosted the 2010 FIFA World Cup by performing a geographically weighted regression between night light data and total city-level income and using it to predict total income from 1992 to 2013. A panel data comparison of income growth in host and non-host cities revealed similar income growth. However, the cities that invested the most in building or renovating their stadia experienced 9% lower income growth than other host cities, suggesting the limited ability of the World Cup to stimulate economic growth and the presence of inefficient investment.